. Operational risk factors and the sustainability of small and medium manufacturing enterprises in South Africa - Urim-Tummim Shipanga; Suzaan Le Roux; Jobo Dubihlela (Insights into Regional Development)
In South Africa, the success of Small and Medium-sized Enterprises (SMEs) is essential in developing the economy as these businesses are known as drivers of economic growth. However, these SMEs have a high failure rate, mainly caused by operational risks. According to Scholarly literature, operational risk is any event that disrupts the normal flow of business processes. It generates financial loss or damage due to operational risk factors: people, process, system and external events. It was further established in South Africa that when these operational risk factors are not controlled, they can adversely impact the sustainability of SMEs. Most of these manufacturing enterprises do not implement operational risk management as they consider it a privilege of large enterprises. These Manufacturing companies must implement operational risk management to mitigate potential threats. This research study aims to investigate the operational risk factors affecting Manufacturing SMEs' sustainability in the Cape Metropole. Quantitative data was acquired from 85 respondents (managers/or owners) of Manufacturing SMEs in the Cape Metropole. Based on the results, it was found that all four of these operational risk factors still affect the sustainability of these business entities. To deal with these operational risk factors effectively, SMEs need operational risk management to identify, minimise and mitigate risks that negatively affect their sustainability.